Mitigation of land degradation at Juana Watershed, Central Java - I B Pramono (Brawijaya University, 2014)
Land degradation became more and more widespread, especially in areas with a dense population and dependence on agriculture is high enough. Land degradation can be approximated by the susceptibility of land to erosion. This study aims to identify existing land degradation in the Juana watershed, Central Java. The method used is the analysis of the typology of the watershed. This method is based on the interaction between landforms and land cover. The results showed that the degradation of land in the watershed very heavy scattered in the upstream areas in the territory of the Kudus and Pati regency. While severe land degradation are also scattered in Kudus, Pati, and Blora regency. Almost all of these degraded areas are used for dry land farming. By knowing the rate of spread of land degradation, the authority having jurisdiction in this district offices on issues related to land degradation can plan the actions necessary to resolve or mitigate land degradation in each region so that a major disaster will not happen or the impact can be minimized.